Consumer Buying Behavior in Kathmandu’s Two-Wheeler Market: A Thematic Review of Determinants and Market Context - Karki, Meen Bahadur; Vyas, Shweta (A Bi-annual South Asian Journal of Research & Innovation, 2025)
This review synthesises existing knowledge on consumer buying behaviour in Kathmandu’s two-wheeler market, integrating literature findings with recent market data. Nepal’s two-wheeler sector has expanded rapidly: approximately 2.6 million of 3.8 million registered vehicles in Nepal are two-wheelers (≈80%). We surveyed over 40 empirical and review studies (primarily from South Asia) and consulted official reports (trade data) to identify purchase drivers. Key influences include product attributes (fuel efficiency, engine performance, design, brand image, safety), socio-economic factors (age, income, gender), and marketing stimuli (pricing, financing schemes, promotions), as well as social influences (family and peer recommendations). For Kathmandu consumers, fuel economy and financing options are especially important, though many buyers rely on informal advice and lack in-depth product knowledge. These findings are contextualised by market statistics (e.g. Bajaj’s 28% share of the market) and suggest that aligning product positioning and financing schemes with consumer priorities can improve market strategies.